Artificial Intelligence and Philosophy of Humanism in Auditor Perceptions - Made Dudy Satyawan; Sri Iswati (Journal of Economics, Business, and Accountancy Ventura, 2023)
This study aims to interpret the humanistic thinking of Chinese philosopher Confucius on the activity of integrating Artificial Intelligence (AI) into the process of auditing financial statements. The qualitative-interpretive method was used for research purposes through in-depth interview techniques which were addressed to informants from audit firms that had used AI. The validity of the information was tested using triangulation of data sources from different audit firm informants. The main findings show that as humans who have cognitive, moral and ethical abilities, auditors can collaborate with AI without worrying that the existence of this profession will be completely replaced by AI. However, excessive integration and tend to rely on auditors should be aware of so that high-tech assisted audit objectives such as AI work in harmony without eliminating the auditor's humanism such as skepticism and professional judgment that AI does not have. Social and ethical issues are challenges in the use of AI and solutions will continue to be sought. Therefore, the auditor always maintains critical thinking, especially on the elements contained in AI technology, namely system predictability, dependability, reliability, robustness, understanding, explanation of intent, usability, and user familiarity with AI technology.